Reduction Mammaplasty in Conjunction with Breast Conservation - Spear, Scott L. (Thieme Medical Publishers, 2004)
Breast conservation therapy, consisting of lumpectomy or segmental mastectomy with negative margins followed by breast irradiation, has become a standard and safe alternative to mastectomy in selected patients with early-stage breast cancer. As the inclusion criteria for breast conservation therapy have continued to evolve to include lower quadrant tumors, very large breasts, and central tumors, the potential for significant disfigurement after breast conservation therapy has increased. Bilateral reduction mammaplasty in conjunction with tumor-directed partial mastectomy is a surgical approach that can benefit these patients by creating symmetric, aesthetically pleasing breasts in a single-stage operation.